A low-cost integrated biosensing platform based on SiN nanophotonics for biomarker detection in urine. Issue 25 (14th June 2018) - Martens, D.; Ramirez-Priego, P.; Murib, M. S.; Elamin, A. A.; Gonzalez-Guerrero, A. B.; Stehr, M.; Jonas, F.; Anton, B.; Hlawatsch, N.; Soetaert, P.; Vos, R.; Stassen, A.; et al.
Abstract : We present a low-cost integrated nanophotonic lab-on-a-chip platform suitable for point-of-care (POC) biomarker analysis. Abstract : We present a low-cost integrated nanophotonic lab-on-a-chip platform suitable for point-of-care (POC) biomarker analysis. The sensor chip included in the platform contains multiplexed Mach–Zehnder interferometers with an on-chip optical spectral analyser consisting of an arrayed-waveguide grating. The sensor chip is fabricated in silicon nitride material, which makes it compatible with consumer-electronics-grade sources and detectors, leading to the possibility of low-cost instrumentation. The nanophotonic sensor chip exhibits a detection limit of 6 × 10 −6 RIU (Refractive Index Units), which is in the same order of magnitude as the reported values for state-of-the-art evanescent wave sensors. The sensor chip is biofunctionalised with specific bioreceptors and integrated into a polymer microfluidic cartridge. The POC instrumentation platform contains optical excitation and read-out sub-systems and dedicated on-board software for real-time analysis of patient samples. To demonstrate the versatility of the platform, we present results both on the detection of an antigen related to tuberculosis directly in urine samples using a laboratory prototype and on the detection of a protein biomarker (CRP) related to inflammation using the integrated instrument.